Bodies of Work: Civic Display and Labor in Industrial Pittsburgh - Rosenow, Michael K. (Labour / Le Travail, 2010)
The article reviews the book, "Bodies of Work: Civic Display and Labor in Industrial Pittsburgh," by Edward Slavishak.
Keywords: BODIES of Work: Civic Display & Labor in Industrial Pittsburgh (Book); BOOKS – Reviews; History; Nonfiction; PITTSBURGH (Pa.); SLAVISHAK; Edward